1994
DOI: 10.1128/jb.176.17.5312-5319.1994
|View full text |Cite
|
Sign up to set email alerts
|

A Streptomyces avermitilis gene encoding a 4-hydroxyphenylpyruvic acid dioxygenase-like protein that directs the production of homogentisic acid and an ochronotic pigment in Escherichia coli

Abstract: A 1.5-kb genomic fragment isolated from Streptomyces averninlis that directs the synthesis of a brown pigment in Eschenichia coli was characterized. Since pigment production in recombinant E. coli was enhanced by the addition of tyrosine to the medium, it had been inferred that the cloned DNA might be associated with melanin biosynthesis. Hybridization studies, however, showed that the pigment gene isolated from S. avermitilis was unrelated to the Streptomyces antibioticus melC2 determinant, which is the proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 47 publications
(40 reference statements)
5
80
1
Order By: Relevance
“…culture both on solid and liquid media [16,7]. The authors found that the intensity of this pigment could be increased by the addition of L-tyrosine.…”
Section: Hppd Activitymentioning
confidence: 83%
See 1 more Smart Citation
“…culture both on solid and liquid media [16,7]. The authors found that the intensity of this pigment could be increased by the addition of L-tyrosine.…”
Section: Hppd Activitymentioning
confidence: 83%
“…The possible role of rat F antigen only came to light when 4HPPD from Streptomyces, human and porcine were cloned [16,18,19]. Sequence comparison showed that RFA bore a striking similarity to 4HPPD isolated from these organisms.…”
Section: Otkicd Activitymentioning
confidence: 99%
“…These melanin pigments are produced on solid medium and then later accumulate in the spores. Another melanin is an ochronotic pigment that is derived from homogentiginic acid and produced in both solid and liquid media (18). Two melanin gene clusters involving tyrosinase were found in the genome (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…pET15b and pET-HPPD were transformed into Escherichia coli cell line BL21(DE3) (Novagen) via electroporation. HPLC analysis of bacterial cultures for the presence of HGA was performed according to published procedures (Denoya et al, 1994). HGA was identified in extracts based on comparison of retention time and spectra to a HGA (Sigma) standard with a Hewlett-Packard series 1100 chromatograph and photodiode array detector.…”
Section: Protein Overexpressionmentioning
confidence: 99%